f(1) -> f(g(1))

f(f(

g(0) -> g(f(0))

g(g(

R

↳Dependency Pair Analysis

F(1) -> F(g(1))

F(1) -> G(1)

G(0) -> G(f(0))

G(0) -> F(0)

Furthermore,

R

↳DPs

→DP Problem 1

↳Narrowing Transformation

→DP Problem 2

↳Nar

**F(1) -> F(g(1))**

f(1) -> f(g(1))

f(f(x)) -> f(x)

g(0) -> g(f(0))

g(g(x)) -> g(x)

On this DP problem, a Narrowing SCC transformation can be performed.

As a result of transforming the rule

no new Dependency Pairs are created.

F(1) -> F(g(1))

The transformation is resulting in no new DP problems.

R

↳DPs

→DP Problem 1

↳Nar

→DP Problem 2

↳Narrowing Transformation

**G(0) -> G(f(0))**

f(1) -> f(g(1))

f(f(x)) -> f(x)

g(0) -> g(f(0))

g(g(x)) -> g(x)

On this DP problem, a Narrowing SCC transformation can be performed.

As a result of transforming the rule

no new Dependency Pairs are created.

G(0) -> G(f(0))

The transformation is resulting in no new DP problems.

Duration:

0:00 minutes